The effect of zinc oxide and Curcuma heyneana Val. combination on stability and sun protection factor (SPF) of lotion - Dian Eka Ermawati; Dita Yuli Budiasih (Pharmaciana, 2022)
Indonesian people risk-averse effects of Ultraviolet (UV) exposure, so they need skin protection agents. Zinc Oxide (ZnO) is an effective UV reflection, but at a concentration of more than 10%, it can cause skin irritation. Combining ZnO with other UV protective agents is necessary, so its concentration can be reduced but still effective. The flavonoid in C. heyneana has potential as a sunscreen because chromophore groups can absorb UV B and UV A light. This study aims to examine the effect of the combination of ZnO and C. heyneana on the stability and SPF value of lotion. The lotion is made in five variations of the composition of ZnO and C. heyneana, F1 of 100: 0%; F2 of 0:100%; F3 of 50:50%; F4 of 25:75%; and F5 of 75:25% respectively. Test parameters include organoleptic, pH, spreadability, viscosity, and SPF. The test is recorded before and after the cycling test. Statistical analysis using Paired Sample T-Test. The combination of ZnO and C. heyneana affected organoleptic, viscosity, spreadability, and SPF value but did not affect pH. The higher concentration of ZnO will increase the viscosity, pH, and SPF but decrease the spreadability. The formula with a combination of ZnO and C. heyneana of 50%:50% is selected because it has an SPF value of 13.24 and; a viscosity of 48.67 d.Pas; pH of 7.1; and spreadability of 3.81 cm.